ANALISIS PENGARUH TRANSACTION COST TERHADAP HOLDING PERIOD SAHAM-SAHAM LQ45 DI BURSA EFEK INDONESIA (BEI) - Ade Nahdiatul (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2016)
This research aim to analysis whether/what there are influence from bid- ask spread, market value, variance return, dividend yield and earning per share to holding period. This research test holding period at shares LQ45 in exchange of Indonesia ( BEI) period 2007-2012. Sample from this research use 12 company which always be enlisted in LQ45. This researching use daily , with calculation of holding period use daily mean during one semester. Used by analysis test t, and doubled regration. Used in this research closing price, sum up share circulate, volume of share commerce, and also bid and ask price. From of result of research of Adjusted R2 obtained value 36,4% variation of explainable holding period by third the variable that is bid-ask spread, market value, variance return, dividend yield and earning per share while 63,6% explained by other;dissimilar variable outside model. While from result test t obtained evidence that variable of market value, and dividend yield have an effect on positive and signification to holding period. That which variable of bid-ask spread, variance return, and earning per share have an effect on negativity and signification n to holding period. Fifth the result have been tested with signification = 5% and most have an effect on to holding period dividend yield. Dari result of test F obtained evidence that bid-ask spread, market value, variance return, dividend yield and earning per share in together have an effect on to holding period share Keyword: bid-ask spread, market value, variance return, dividend yield, earning per share and holding period.